Some New Ecological Aspects of the Lesser Sunda Endemic Drepanosticta berlandi (Odonata: Zygoptera: Platystictidae) - Zulhariadi, Muhammad; Nugroho, Muhammad Setyo; Hidayani, Nurul (Makara Journal of Science, 2025)
Drepanosticta berlandi is an endemic damselfly in the Lesser Sunda region of Indonesia, which was first recorded on Lombok Island in the 19th century. Albeit recognized for a century, information on its ecology is still lacking; hence, this study aims to reveal its distribution and habitat preferences. The research was conducted at the Tibu Ijo Waterfall tourist area in West Lombok Regency using line transects combined with field survey in the Kekait River and on footpaths on both sides of the river. Vegetation density, topography, and land survey temperature (LST) were measured at the sampling area using ArcGIS 10.4.1 software. Other environmental parameters (air temperature and humidity, CO2 levels, light intensity, height, canopy cover, water temperature, pH, total dissolved solids (TDS), and electrical conductivity (EC)) were measured in situ. The results show that D. berlandi has a clumping distribution pattern in the elevation range of 60 to 220 m, preferring medium vegetation density and cool air temperatures (22–26 °C). Disturbances from human activities and environmental changes pose a significant threat to the D. berlandi population. Therefore, this species represents a bioindicator of environmental intactness, especially on the island of Lombok.